PARTISIPASI MASYARAKAT TERHADAP PENGEMBANGAN DESA WISATA OKURA DI KELURAHAN TEBING TINGGI KECAMATAN RUMBAI TIMUR KOTA PEKANBARU - ", Dzikriansyah; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the level of community participation in the development of Okura Tourism Village and to determine the factors that influence community participation in the development of Okura Tourism Village, high cliffs Okura village, Rumbai East District, Pekanbaru City. The method in this researc is descriptive quantitative. The population in this study amounted to 72 families and the sample obtained using the Slovin formula amounted to 61 respondents. Data collection techniques and questionnaires. The data analysis technique uss Validity test, Reliabiliti test, then uses the interval formula to determine the level of community participation and to determine the factors that influence community participation in the development of Okura Tourism Village. The conclusion is that the level of community participation in the development of tourist villages is high with an average score of 68,64% and the factors that influence community participation in the development of tourist villages are supporting factors, inhibiting factors, and tourism village development.  Keywords: Participation Rate, Community, Tourism Village